Meat Consumption and Cerebrovascular Disease An Updated Review of Stroke Risk and Mortality - Czmyr, Jędrzej; Marczak, Zuzanna; Sito, Maksymilian; Jurkowski, Filip; Wójcik, Łukasz; Gawron, Natalia; Bojanowski, Hubert Tomasz; Dobracka, Aleksandra; Zachar, Kinga; Jarowicz, Monika (Quality in Sport, 2026)
Introduction and aim of the study Strokes are a leading cause of global mortality and disability. While diet is a key modifiable risk factor, the impact of specific proteins requires clarification. This review evaluates evidence on how unprocessed red meat, processed meat, white meat, and fish affect stroke risk to inform dietary guidelines. Materials and methods A literature search of PubMed, Embase, and the Cochrane Library focused on large-scale meta-analyses, prospective cohort studies, and established pathophysiology linking specific meat types with stroke outcomes. State of Knowledge Evidence shows a distinct stroke risk gradient by meat type. Processed meat is a potent risk factor; a 50g/day intake raises stroke risk by 11–17%, driven by sodium and nitrites inducing hypertension. Unprocessed red meat shows a modest association; a 100g/day increase is linked to an 11–13% higher ischemic stroke risk, likely mediated by heme iron and the gut metabolite TMAO. Conversely, white meat has a neutral or slightly protective effect. Fish offers robust protection; its consumption reduces stroke risk by 14%, attributed to marine n-3 polyunsaturated fatty acids. Conclusions Protein choices significantly influence stroke risk. Limiting processed and unprocessed red meats, and substituting them with fish or white meat, is an effective stroke prevention strategy. Further research should clarify the impact of preparation methods and specific stroke subtypes.